The Changing Face of Early-onset Neonatal Sepsis After the Implementation of a Maternal Group B Streptococcus Screening and Intrapartum Prophylaxis Policy-A Study in One Medical Center - Chia-Ying Lin; Chyong-Hsin Hsu; Fu-Yuan Huang; Jui-Hsing Chang; Han-Yang Hung; Hsin-An Kao; Chun-Chih Peng; Wai-Tim Jim; Hsin Chi; Nan-Chang Chiu; Tung-Yao Chang; Chen-Yu Chen; et al. (Elsevier, 2011)
Early-onset sepsis (EOS) is the major cause of neonatal morbidity and mortality. Maternal group B Streptococcus (GBS) screening and intrapartum antibiotic prophylaxis (IAP) were implemented in our hospital in 2004. Our aim was to evaluate the effectiveness of the program and changes in pathogens and antibiotic susceptibility. Methods: The medical charts of mothers and infants with EOS between January 2001 and November 2008 were retrospectively reviewed. EOS was defined as sepsis occurring within 72 hours of birth. Data were pooled and compared for January 2001 through September 2004 (Period 1, without GBS screening) and October 2004 through November 2008 (Period 2, with GBS screening and IAP). Results: The GBS screening rate increased from 10.11% in 2004 to 65% in 2008 and the IAP rate increased from 40% in 2004 to 90% in 2008. The most common EOS pathogen in Period 1 was GBS (45.4%), which decreased to 20% in Period 2 (p=0.081; trend p=0.009). The percentage of EOS because of Escherichia coli in Period 1 was 40.9% but increased to 70% in Period 2 (p=0.059). E coli EOS increased in extremely low birth weight premature babies weighing 500-1000 g from Period 1 to Period 2 (p=0.031). The incidence of ampicillin-resistant E coli EOS was relatively high, but no significant change (88.9% vs. 92.9%) after implementation of GBS screening and IAP was noted. Conclusion: GBS screening plus IAP is effective in decreasing the incidence of GBS EOS; however, an increase in EOS caused by E coli was noted. Monitoring of pathogens causing EOS is important for effective treatment.